The Changes Impact on State Ministries Nomenclature Toward National Development Progress - Nasution, Ali Imran (Veteran Law Review, 2021)
The government is given the responsibility to performing national development in order to pursue national goals as the establishment of Indonesia. As head of government, President is assisted by ministers to carry out national development. However, the already formed state ministries frequently had to change its nomenclature amidst President's leadership. Changes in ministries nomenclature generally occur due to merger or splitting of ministries. This study aims to understand the regulation of changing ministries nomenclature and how it will affected national development. The methodology uses in this study is normative research by statutory and conceptual approach. The results indicate that the timing of changing ministry's nomenclature raises ambiguity. Changes in ministries nomenclature amidst of President's leadership have affected on ministry's work programs implementation that have been prepared by prior ministries.